English for automotive industry: Mempersiapkan generasi muda untuk karir global di industri otomotif - Putri, Mas Fierna Janvierna Lusie; Handayani, Sri Rahayu; Amirin, Amirin; Marvianto, Rachmat Anggi; Arafat, Yunus Bakhtiar; Haq, Syauqie Dhiyaul; Maulana, Fahmi (Nur Science Institute, 2025)
The global automotive industry demands a workforce that possesses not only technical skills but also the ability to communicate professionally in English. Unfortunately, many high school graduates still struggle to understand technical terms, express ideas professionally, and write work-related reports in English. This community service program aimed to improve the job readiness of students at SMA Chandra Buana through English language training based on the context of the automotive industry. The activity was carried out on January 31, 2025, involving 16 students from grades X and XI IPS. The training covered technical vocabulary introduction, vehicle manual reading, workplace communication simulations, technical report writing, and oral presentations. Evaluation using pre-tests and post-tests showed an improvement in technical English comprehension. In addition, students’ confidence in using English also increased significantly. This program makes a tangible contribution to preparing students for the global job market and emphasizes the importance of English learning based on industrial context at the secondary education level.